(untitled) (Research, Society and Development, 2022)
Erythrocyte Sedimentation Velocity (ESR) is a simple and routine laboratory investigation method in the veterinary clinic for the evaluation of infectious-inflammatory processes and a general indicator of animal welfare. In a systematic review, we evaluated the surroundings of the sensitivity potential of the ESR in the diagnosis of different pathologies in horses. Therefore, a careful search was carried out in Pubmed, ScienceDirect, Scopus, Web of Science and SciELO databases for randomized clinical trials until 2021, which culminated in the literary review of five studies. We evidenced five breeds of horses evaluated through ESR methodologies that varied between the standard Westergren method or the modified Westergren method, with the use of different anticoagulants, such as: ethylenediamine tetraacetic acid (EDTA), citrate and heparin. The ESR showed diagnostic sensitivity and positive correlation with complementary laboratory parameters, such as: hemoglobin, plasma proteins, leukocyte count and red blood cell count. We also emphasize the need for studies with other races and modulations of stress and pathological conditions, especially covering other nationalities and the peculiarities in which they are inserted.